The role of interleukin-1 in general pathology - Naoe Kaneko; Mie Kurata; Toshihiro Yamamoto; Shinnosuke Morikawa; Junya Masumoto (BMC, 2019)
Abstract Interleukin-1, an inflammatory cytokine, is considered to have diverse physiological functions and pathological significances and play an important role in health and disease. In this decade, interleukin-1 family members have been expanding and evidence is accumulating that highlights the importance of interleukin-1 in linking innate immunity with a broad spectrum of diseases beyond inflammatory diseases. In this review, we look back on the definition of "inflammation" in traditional general pathology and discuss new insights into interleukin-1 in view of its history and the molecular bases of diseases, as well as current progress in therapeutics.